Amphiphilic AIEgen‐polymer aggregates: Design, self‐assembly and biomedical applications. Issue 1 (21st October 2021) - Cao, Shoupeng; Shao, Jingxin; Abdelmohsen, Loai K. E. A.; van Hest, Jan C. M.
Abstract: Aggregation‐induced emission (AIE) is a phenomenon in which fluorescence is enhanced rather than quenched upon molecular assembly. AIE fluorogens (AIEgens) are flexible, conjugated systems that are limited in their dynamics when assembled, which improves their fluorescent properties. This intriguing feature has been incorporated in many different molecular assemblies and has been extended to nanoparticles composed of amphiphilic polymer building blocks. The integration of the fascinating AIE design principle with versatile polymer chemistry opens up new frontiers to approach and solve intrinsic obstacles of conventional fluorescent materials in nanoscience, including the aggregation‐caused quenching effect. Furthermore, this integration has drawn significant attention from the nanomedicine community, due to the additional advantages of nanoparticles comprising AIEgenic molecules, such as emission brightness and fluorescence stability. In this regard, a range of AIEgenic amphiphilic polymers have been developed, displaying enhanced emission in the self‐assembly/aggregated state. AIEgenic assemblies are regarded as attractive nanomaterials with inherent fluorescence, which display promising features in a biomedical context, for instance in biosensing, cell/tissue imaging and tracking, as well as (photo) therapeutics. In this review, we describe recent strategies for the design and synthesis of novel types of AIEgenic amphiphilic polymers via facile approaches including direct conjugation to natural/synthetic polymers, polymerization, post‐polymerization and supramolecular host−guest interactions. Their self‐assembly behavior and biomedical potential will be discussed. Abstract : The recent advances in the design and synthesis of AIEgenic amphiphilic polymers are discussed. Their self‐assembly leads to particles with very high fluorescence intensity. The versatility of polymer science allows the creation of a wide variety of particles which show much potential for biomedical applications.